Proceedings of the 13th International Conference on Human Computer Interaction With Mobile Devices and Services 2011
DOI: 10.1145/2037373.2037400
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and bridges in the adoption of today's mobile phone contextual services

Abstract: This paper presents ethnographic observations, a diary study and a large-scale quantitative questionnaire (n=395) designed to study the reasons for adoption and refusal of contextaware mobile applications. Through a qualitative study we identify 24 user needs that these applications fulfill and 9 barriers for adoption. We found that for many of the identified needs the end-goal is not that of receiving information, thus complementing work on mobile information needs. Also, this work offers an actionable list o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Recent work by Cherubini et al [2011] has revealed that the lack of personalization is actually one of the biggest barriers for the adoption of today's mobile phone contextual services. Our findings support these conclusions and further identify new opportunities for personality-based personalization.…”
Section: Consider Personality-based Personalizationmentioning
confidence: 99%
“…Recent work by Cherubini et al [2011] has revealed that the lack of personalization is actually one of the biggest barriers for the adoption of today's mobile phone contextual services. Our findings support these conclusions and further identify new opportunities for personality-based personalization.…”
Section: Consider Personality-based Personalizationmentioning
confidence: 99%
“…While many users appreciate the value of targeted services in mobile devices, they still express concern over how their data is collected and managed without their knowledge. For example, Cherubini et al [13] identify privacy as a barrier to the adoption of mobile phone context services. 70% of consumers say it is important to know exactly what personal information is being collected and shared [14], while 92% of users expressed concern about applications collecting personal information without their consent [15].…”
Section: Related Workmentioning
confidence: 99%
“…Some authors have implicitly associated information needs with information that is typically searched and obtained via the mobile Internet [Church and Smyth 2009;Hinze et al 2010] or with whether the person expressing the need could recall the information [Heimonen 2009]: "need for a piece of information that you cannot recall from memory or that is not immediately available to you." Recently, other researchers have restricted their studies to information needs that could be fulfilled by mobile phones only [Chua et al 2011] or enlarged the scope of their investigation to needs whose goals go beyond increasing one's personal knowledge about things [Cherubini et al 2011]. Thus, this past work highlights the lack of a single, consistent notion of an information need.…”
Section: Definition Of Information Needsmentioning
confidence: 99%
“…They collected 204 entries that were organized into 10 categories. Cherubini et al [2011] conducted a 3-week video and paper diary study on information needs of 8 smartphone users of contextual applications (e.g., a navigation application). They collected 114 diary entries, several hours of video diary entries, and recordings of interviews.…”
Section: Types Of Information Needsmentioning
confidence: 99%